Photochemical modifications for DNA/RNA oligonucleotides. Issue 11 (24th February 2022) - Tavakoli, Amirrasoul; Min, Jung-Hyun
Abstract : Photoconvertible groups (PG) can be incorporated into an oligonucleotide to undergo various irreversible and reversible light-induced reactions such as cleavage, crosslinking, isomerization, and intramolecular cyclization reactions. Abstract : Light-triggered chemical reactions can provide excellent tools to investigate the fundamental mechanisms important in biology. Light is easily applicable and orthogonal to most cellular events, and its dose and locality can be controlled in tissues and cells. Light-induced conversion of photochemical groups installed on small molecules, proteins, and oligonucleotides can alter their functional states and thus the ensuing biological events. Recently, photochemical control of DNA/RNA structure and function has garnered attention thanks to the rapidly expanding photochemistry used in diverse biological applications. Photoconvertible groups can be incorporated in the backbone, ribose, and nucleobase of an oligonucleotide to undergo various irreversible and reversible light-induced reactions such as cleavage, crosslinking, isomerization, and intramolecular cyclization reactions. In this review, we gather a list of photoconvertible groups used in oligonucleotides and summarize their reaction characteristics, impacts on DNA/RNA thermal stability and structure, as well as their biological applications.